The Russians at Merv and Herat, and their power of invading India. - Marvin, Charles (W. H. Allen & co., 1883)
The Russians at Merv and Herat, and Their Power of Invading India is an account of Russian policy in Central Asia and of possible Russian intentions toward Afghanistan and India in the late 19th century, written from a British perspective. Topics covered include writings by Russian military officers on Central Asia and India; the analysis by the Russian general staff of the Second Anglo-Afghan War (1878-80); the journeys by Russian diplomat Pavel M. Lessar from Ashgabad (present-day Ashqabat, Turkmenistan) to Sarakhs (in present-day Iran) and from Sarakhs to Herat, Afghanistan; Russian railroad construction in Central Asia; Russia's buildup of naval power in the Caspian Sea; and the development of the oil industry in Baku (present-day Azerbaijan). The book predicts that in a future crisis with Great Britain, Russia, unlike in previous crises or during the Crimean War, almost certainly would strike at British India. The author, Charles Thomas Marvin (1854-90), was a writer and one-time Foreign Office staff member who had lived many years in Russia, initially with his father, who was employed in Saint Petersburg, and later as a correspondent for a British newspaper. The book draws on interviews that Marvin conducted in 1882 with leading Russian military and political leaders, and contains translations of long excerpts from relevant Russian books and reports. It includes drawings by Russian artists, which, the author asserts, "are the first illustrations of Merv and the Turcoman region that have yet appeared in this country." The book contains three appendices, including a long essay on the Russian navy that is only partly related to the main subject of the work.World Digital Library.
Bk.1. General Annenkoff on Russia in Central Asia and England in India -- bk.2. The Russian general staff on the Afghan War and English weakness in India -- bk. 3. Russian pioneers beyond the Caspian -- bk. 4. The Russians beyond the Caspian -- Appendices: 1. Russian cruisers and English communications with India -- 2. The rival Turkestan and Caucasian movements towards India -- 3. English exploration of Merv.
The Russians at Merv and Herat, and Their Power of Invading India is an account of Russian policy in Central Asia and of possible Russian intentions toward Afghanistan and India in the late 19th century, written from a British perspective. Topics covered include writings by Russian military officers on Central Asia and India; the analysis by the Russian general staff of the Second Anglo-Afghan War (1878-80); the journeys by Russian diplomat Pavel M. Lessar from Ashgabad (present-day Ashqabat, Turkmenistan) to Sarakhs (in present-day Iran) and from Sarakhs to Herat, Afghanistan; Russian railroad construction in Central Asia; Russia's buildup of naval power in the Caspian Sea; and the development of the oil industry in Baku (present-day Azerbaijan). The book predicts that in a future crisis with Great Britain, Russia, unlike in previous crises or during the Crimean War, almost certainly would strike at British India. The author, Charles Thomas Marvin (1854-90), was a writer and one-time Foreign Office staff member who had lived many years in Russia, initially with his father, who was employed in Saint Petersburg, and later as a correspondent for a British newspaper. The book draws on interviews that Marvin conducted in 1882 with leading Russian military and political leaders, and contains translations of long excerpts from relevant Russian books and reports. It includes drawings by Russian artists, which, the author asserts, "are the first illustrations of Merv and the Turcoman region that have yet appeared in this country." The book contains three appendices, including a long essay on the Russian navy that is only partly related to the main subject of the work.World Digital Library.
Keywords: Eastern question (Central Asia); Russians / Asia, Central